2019
DOI: 10.1177/1367549418823058
|View full text |Cite
|
Sign up to set email alerts
|

Transatlantic repatriation: Stigma management of second-generation Italian and Greek American women ‘returning home’

Abstract: Based on 30 narrative-biographic interviews with second-generation Greek and Italian women who have migrated from the USA to their ancestral homelands of Greece and Italy, our paper explores nuances of their stigma management by focusing on the interaction between their pre-repatriation past and post-repatriation present and the spaces of inclusion and exclusion. We investigate from the insider perspective the interplay between returnee-women's rejection and acceptance of stigma and, particularly, their use of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Shortland and Perkins (2020) found that early-career stage female expatriates believe that equality/diversity policy implementation will support their international careers while senior levels female expatriates highlighted unequal treatment, breaching trust in delivery of equality/diversity principles affect their career progression. Others female expatriate articles systematically analysed include (Shortland, 2020;Isaakyan and Triandafyllidou, 2019;Shortland and Perkins, 2016;Shortland, 2016;Shortland 2014).…”
Section: Literature Classification Discussion Of Findings and Future ...mentioning
confidence: 99%
“…Shortland and Perkins (2020) found that early-career stage female expatriates believe that equality/diversity policy implementation will support their international careers while senior levels female expatriates highlighted unequal treatment, breaching trust in delivery of equality/diversity principles affect their career progression. Others female expatriate articles systematically analysed include (Shortland, 2020;Isaakyan and Triandafyllidou, 2019;Shortland and Perkins, 2016;Shortland, 2016;Shortland 2014).…”
Section: Literature Classification Discussion Of Findings and Future ...mentioning
confidence: 99%
“…The reputation repair strategies traitors, criminals, those with physical deformities, and even migrants (Isaakyan and Triandafyllidou, 2019;Pescosolido and Martin, 2015). This allegorical use of the word 'stigma', however, resonated with some scholars who have found relevance for the word as a concept to explore the emergence and enactment of identities that are perceived by some social audiences as deviating from the expected social identity (Ashforth and Kreiner, 1999;Sutton and Callahan, 1987;Goffman, 1963).…”
Section: Organisational Stigmamentioning
confidence: 99%
“…Tracing the etymology of the word “stigma” takes a curious mind on a retrospective journey to an era where the word was used to identify bodily marks such as cuts, scars, or burns. These marks were often associated with individuals with lower social status, such as slaves, traitors, criminals, those with physical deformities, and even migrants (Isaakyan and Triandafyllidou, 2019; Pescosolido and Martin, 2015). This allegorical use of the word ‘stigma’, however, resonated with some scholars who have found relevance for the word as a concept to explore the emergence and enactment of identities that are perceived by some social audiences as deviating from the expected social identity (Ashforth and Kreiner, 1999; Sutton and Callahan, 1987; Goffman, 1963).…”
Section: Organisational Stigmamentioning
confidence: 99%